1994
DOI: 10.1017/s0022112094001989
|View full text |Cite
|
Sign up to set email alerts
|

Physics of unsteady blunt-fin-induced shock wave/turbulent boundary layer interactions

Abstract: Fluctuating wall-pressure measurements have been made on the centreline upstream of a blunt fin in a Mach 5 turbulent boundary layer. By examining the ensemble-averaged wall-pressure distributions for different separation shock foot positions, it has been shown that local fluctuating wall-pressure measurements are due to a distinct pressure distribution, [weierp ]i, which undergoes a stretching and flattening effect as its upstream boundary translates aperiodically between the upstream-influence and separatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
42
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 15 publications
7
42
0
Order By: Relevance
“…A decrease of the frequency scale appear when the shock is stronger. We can notice an analogous evolution for the compression ramp case [2]. For comparison we can define a Strouhal number S L = f L/U ∞ , based on the interaction length L and on the external upstream velocity U ∞ .…”
Section: Scales Of Space and Time On The Interaction Centre Linementioning
confidence: 87%
See 1 more Smart Citation
“…A decrease of the frequency scale appear when the shock is stronger. We can notice an analogous evolution for the compression ramp case [2]. For comparison we can define a Strouhal number S L = f L/U ∞ , based on the interaction length L and on the external upstream velocity U ∞ .…”
Section: Scales Of Space and Time On The Interaction Centre Linementioning
confidence: 87%
“…Reference is made to recent experimental, computational and analytical work on this question. On the experimental side, results have already been obtained in this field by Doerffer and Dallmann [7], Thomas et al [21], Brusniak and Dolling [2] for example. Most of the classical references can be found in Smits and Dussauge [20] and in recent reviews by Dolling [8] and Lee [17], and also by Delery [5].…”
Section: Introductionmentioning
confidence: 83%
“…The most commonly considered interactions concern those with a turbulent boundary layer, although laminar or transitional interactions have also been investigated in the literature. Cases under consideration cover a large range of geometric configurations, including normal shock interactions (Atkin & Squire 1992;Bruce & Babinsky 2008;Bur et al 2008), blunt fin interactions (Brusniak & Dolling 1994;Ünalmis & Dolling 1996;Bueno 2006), over-expanded nozzles (Frey & Hagemann 1998, 2000Bourgoing & Reijasse 2005), compression ramp interactions (Thomke & Roshko 1969;Spaid & The characteristic length L used in the Strouhal number represents the effects of the presence of the boundary layer in comparison to a purely inviscid flow (see the scheme in figure 1). It is defined as the observed upstream shift of the shock wave C S due to the thickening of the boundary layer, subject to the imposed pressure jump (or equivalently the angle of deviation of the flow).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Erengil and Dolling's 9 studies of separation shock foot unsteadiness showed a correlation between the wall pressure fluctuations beneath the incoming boundary layer and the shock foot velocity, from which it was inferred that the small-scale motion of the shock is caused by its response to the convection of turbulent fluctuations through the interaction. Their work also demonstrated that the large-scale motion is a result of the shock's displacement due to the expansion and contraction of the separation bubble.…”
Section: Introductionmentioning
confidence: 99%